1993
DOI: 10.2307/3431838
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Origin of Cancer: Dedifferentiation or Stem Cell Maturation Arrest?

Abstract: Given the fundamental principle that cancer must arise from a cell that has the potential to divide, two major nonexclusive hypotheses of the cellular origin of cancer are that malignancy arises a) from stem cells due to maturation arrest or b) from dedifferentiation of mature cells that retain the ability to proliferate. The role of stem cells in carcinogenesis is clearly demonstrated in teratocarcinomas. The malignant stem cells of teratocarcinomas are derived from normal multipotent stem cells and have the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(83 citation statements)
references
References 33 publications
4
78
0
1
Order By: Relevance
“…Review articles have suggested that malignancy could arise either from stem cells due to a maturation arrest, or from a dedifferentiation of mature cells that regain the ability to proliferate [43,44]. Although present considerations about gastric carcinogenesis usually prefer the stem cell hypothesis, a definite proof of it is lacking [14].Our study suggests that an origin of gastric carcinomas from dedifferentiated gastric cells is also possible.…”
Section: Discussionmentioning
confidence: 92%
“…Review articles have suggested that malignancy could arise either from stem cells due to a maturation arrest, or from a dedifferentiation of mature cells that regain the ability to proliferate [43,44]. Although present considerations about gastric carcinogenesis usually prefer the stem cell hypothesis, a definite proof of it is lacking [14].Our study suggests that an origin of gastric carcinomas from dedifferentiated gastric cells is also possible.…”
Section: Discussionmentioning
confidence: 92%
“…The ‘maturation arrest’ hypothesis [27] states that genetic alterations occurring in a hepatic progenitor, or its immediate progeny, cause aberrant proliferation and prevent its normal differentiation. Further accumulation of genetic alteration can eventually lead to malignant transformation of these incompletely differentiated cells.…”
Section: Introductionmentioning
confidence: 99%
“…The abnormality involving differentiation might be either arrest of the maturation of stem cells, or dedifferentiation of mature cells which retain their ability to proliferate [16]. However, detailed comparisons of cell lines taken from the same primary tumours showed that there are often marked differences in the metastatic capabilities of these proliferating cells.…”
Section: Tumor Cell Heterogeneity and Its Basis Of Genetic Instabilitymentioning
confidence: 97%
“…Tumours are characterised by variable degrees of incomplete differentiation-related change of appearance. This has been discussed in terms of dedifferentiation, or stem cell arrest [16]. Either process could be affected by genetic instability in terms of randomly variable modifications of the genes required for the relevant steps.…”
Section: Differentiationmentioning
confidence: 99%